International economics - Dunn, Robert M.; Mutti, John H. (London ; New York : Routledge, 2004)
This latest edition improves and builds upon the features of previous editions. With impressive pedagogy, learning objectives and summaries, this clearly written book will be another winner with students of international economics and business.
Commercial policy: history and recent controversiesInternational mobility of labor and capital; Trade and growth; Issues of international public economics; International finance and open economy macroeconomics; Balance-of-payments accounting; Markets for foreign exchange; International derivatives: foreign exchange forwards, futures, and options; Alternative models of balance-of-payments or exchange-rate determination; Payments ad.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: International economic relations; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Economics; International economic relations; International economic relations